Pengaruh Sikap, Kesadaran Wajib Pajak, Insentif Pembayaran PBB, dan Pengetahuan Perpajakan terhadap Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan - Natalia, Natalia; Subagyo, Subagyo (Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to examine the effect of attitude, taxpayer awareness, PBB payment incentives, and tax knowledge on taxpayer compliance in paying land and building tax. In this study, the author uses a snowball sampling technique is where researchers start with several initial respondents who meet the research criteria and then ask respondents to recommend other respondents who also meet the criteria. Data were obtained by distributing questionnaires to taxpayers in DKI Jakarta and will be processed using SPSS version 25. The results will determine that the effect of taxpayer awareness, PBB payment incentives, and tax knowledge significantly affects taxpayer compliance in paying land and building tax, but attitudes do not significantly affects taxpayer compliance in paying land and building tax.